The TRAPD approach as a method for questionnaire translation - Walde, Peggy; Völlm, Birgit Angela (Frontiers in Psychiatry, 2023)
Surveys and questionnaires are widely used in various areas of psychological and psychiatric research and practice. Many instruments have been used in several languages and across cultural contexts. For translating them into another language translation and back-translation is a popular method of choice. Unfortunately, this method’s ability to detect flaws in translation and necessities for cultural adaptation is limited. To address these short-comings another method for questionnaire translation known from cross-cultural survey design, the so-called TRAPD approach (Harkness 2011), has been developed. The letters of TRAPD stand for the steps of the process – Translation, Review, Adjudication, Pretest, and Documentation. In this approach, several translators with different professional backgrounds translate the questionnaire on their own first and then come together to discuss their versions. Since the translators’ expertise is required to vary (e.g., survey methodology experts, translation experts, expert knowledge in the questionnaire’s topic) the team approach results in a high-quality translation as well as offering opportunities for cultural adaptation. This article illustrates the application of the TRAPD approach on the basis of the translation process of the Forensic Restrictiveness Questionnaire (Tomlin 2019) from English into German. Differences and advantages are discussed.